Penerapan Metode Design Thinking untuk Perancangan Prototipe Learning Management System Prakerja di HiColleagues - Handika Wahyu Jatmiko; Yudi Wibowo; Arif Yulianto (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Indonesia is predicted to have the threat of demographic bonus while also having the opportunity to take advantage of this threat through the Prakerja program. Since 2020 the Prakerja program has been running and there are still many numerical achievements that need to be realized to avoid the threat of demographic bonus and in line with the vision of Indonesia emas 2025. PT Generasi Anak Muda Berkarya with HiColleagues brand is a startup moving in the field of Education Technology and IT Service in sustainable digital transformation that is committed to realizing the vision of Indonesia emas 2045 through implementation of the Prakerja program. Learning Management System (LMS) platform according to the Prakerja standard is a mandatory requirement that the training institution must have to become the Prakerja partner. This research aims to produce the Learning Management System (LMS) prototype design according to the Prakerja standard, giving a good experience to participants in completing a series of training class mechanisms, support the participant graduation ratio, and increase brand positioning of HiColleagues as the Prakerja partner. Designing a Learning Management System (LMS) prototype applies the Design Thinking method through the 5 phases, namely Empathize, Define, Ideate, Prototype, & Test. As well as using Figma as a design tool and Maze as a Usability Testing. This Learning Management System (LMS) prototype design succeeded in getting good feedback from users with 100% succession rate although there are minor improvisations on the user interface as a form of alignment.